Notary's responsibilities in preventing the crime of money laundering by applying the principles of knowing the service user - Siddiqiyah, Arofatus; Irwan Santosa; Iskandar Muda (Jurnal Info Sains : Informatika dan Sains, 2024)
The purpose of this research is to know and analyze the legal responsibility of Notary in applying the principle of knowing the service user related to the prevention of money laundering and the legal consequences if the Notary does not apply it related to the deed he made. Notaries have a big role and responsibility in carrying out a legal action because they must always act according to their principles, namely prudence in making authentic deeds, Notaries must be able to examine all relevant facts in their considerations based on applicable laws and regulations. This research uses normative legal research methods with the approach of laws and regulations, norms and doctrines as the main study. The results show that the application of the principle of recognizing service users by Notaries regulated in Permenkumham Number 9 of 2017 which is another authority of Notaries regulated outside the UUJN obtained by attribution and the authority aims to contribute to the government in order to anticipate and eradicate money laundering in Indonesia. Because the application of the principle of recognizing service users is an authority that must be implemented, the legal consequences if proven not to apply it will be subject to sanctions in accordance with the provisions of Article 85 of the Law on Notaries.